The Role Of Musyrifah In Shaping The Islamic Personality Of Santriwati At Pondok Pesantren Tahfidzul Qur'an Al Azzaam Semarang - Aviena Sabila Anwar; Rokimin; Deli Amarta (CV Putra Publisher, 2026)
This study analyses the role of musyrifah, the female dormitory supervisors, in shaping the Islamic personality of santriwati at Pondok Pesantren Tahfidzul Qur'an Al Azzaam Semarang, examines the guidance methods applied, and identifies the supporting and inhibiting factors of the process. A descriptive qualitative design with an embedded single case study orientation was employed, positioning the researcher as the key instrument. Data were gathered through participatory observation, in-depth semi-structured interviews with the head of the female dormitory, five musyrifah, santriwati of grades seven and eight, and officials of the santri organisation, complemented by documentation of monthly evaluation checklists, night-attendance records, and coordination minutes. Analysis followed the interactive model of condensation, display, and verification, while credibility was maintained through source and technique triangulation, prolonged engagement, and member checking. The findings show that musyrifah function as an integrated axis of four roles, namely educator, mentor, caregiver, and counsellor-motivator, enacted through exemplary conduct, habituation, checklist-based supervision, personal advice, and a proportionate reward-and-punishment system. Discipline built in the dormitory corresponds directly with the focus and achievement of santriwati in the tahfidz halaqah. Delegating technical supervision to the santri organisation reduces the dual workload of musyrifah while cultivating leadership. Islamic personality formation therefore requires a layered twenty-four-hour nurturing system in which the psychological wellbeing of musyrifah is a strategic prerequisite.